2022
DOI: 10.6018/reifop.511551
|View full text |Cite
|
Sign up to set email alerts
|

Perspectiva de género y condiciones de aprendizajes virtuales en pandemia

Abstract: The adaptations that higher education had to incorporate as a result of the COVID-19 pandemic revealed several weaknesses, shortcomings, and vulnerabilities present in the teaching-learning process; likewise, the student's difficulties in successfully carrying out their professional training were made evident. Much research, even before this public health emergency, has shown gaps in education in regard to gender, with women often facing the greatest impediments regarding access and opportunities. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding the results of Posso [31], they found that women face disadvantages compared to men in terms of access to technological resources and adequate spaces for study. This finding highlights the importance of addressing these barriers and ensuring equitable access to resources and technologies for all students, regardless of their gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the results of Posso [31], they found that women face disadvantages compared to men in terms of access to technological resources and adequate spaces for study. This finding highlights the importance of addressing these barriers and ensuring equitable access to resources and technologies for all students, regardless of their gender.…”
Section: Discussionmentioning
confidence: 99%
“…Bowman [30] found that female students performed better relative to male students in college courses such as mathematics, statistics, and computer science. The disadvantages of female students in learning conditions can affect academic performance and career completion, so it is necessary to deepen the understanding of gender disparities to prevent and mitigate this problem [31].…”
Section: Introductionmentioning
confidence: 99%